2017
DOI: 10.15171/ps.2017.36
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Solvent Effect (Methanol: Water Mixture) on the Phenolic Content and Antioxidant Activities of Stachys turcomanica Trautv

Abstract: A B S T R A C TBackground: The genus of Stachys with 300 species belongs to Lamiaceae family and this genus has 34 species in Iran. Stachys turcomanica Trautv is native to Iran and it used for treatment of infectious, rheumatic and inflammatory diseases in traditional medicine. The effect of solvent (methanol in water: 0, 20, 50, 80 and 100 %) on the extraction of antioxidant compounds from S. turcomanica were investigated using various in vitro assays. Methods: The antioxidant activities of extracts were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
(31 reference statements)
2
4
0
Order By: Relevance
“…According to Ghimire et al (2011), the existence of bioactive chemicals such as phenolics, flavonoids, and tannins in different plant sections could reflect the varying scavenging activities. The perusal of available literature indicates a clear link between the radical scavenging ability of plant extracts and phytochemical contents (Arumugam et al, 2019(Arumugam et al, , 2020Namvar et al, 2017). The current findings also support the view of Yingming et al (2004), who found that extracts with a high phenolic content were more effective in scavenging free radicals.…”
Section: Dpph Radical Scavenging Ac Vitysupporting
confidence: 87%
“…According to Ghimire et al (2011), the existence of bioactive chemicals such as phenolics, flavonoids, and tannins in different plant sections could reflect the varying scavenging activities. The perusal of available literature indicates a clear link between the radical scavenging ability of plant extracts and phytochemical contents (Arumugam et al, 2019(Arumugam et al, , 2020Namvar et al, 2017). The current findings also support the view of Yingming et al (2004), who found that extracts with a high phenolic content were more effective in scavenging free radicals.…”
Section: Dpph Radical Scavenging Ac Vitysupporting
confidence: 87%
“…37 Previously, a strong correlation has been observed between radical scavenging power of plant extract with total phenolics and flavonoids contents. 24 The present results provided evidence that most extracts with high contents of phenolics exhibited greater potency to scavenge free radicals. may also contribute to scavenging capacity.…”
Section: Discussionsupporting
confidence: 59%
“…23 Hence, a proper solvent system has to be used for extraction of maximum amounts of potent antioxidant components from typical plant materials. 24 On the one hand; medicinal plants produce secondary metabolites that are responsible for their therapeutic properties. On the other hand, quality and quantity of these molecules and conversely their activities are affected by environmental factors like geographical locations and origin of plants.…”
Section: Discussionmentioning
confidence: 99%
“…SP1's methanolic and 50% methanolic extracts exhibited higher AGI activity than its water extract (Table 1). Methanol has the ability to extract more secondary metabolites from plants, which were the target compounds in this analysis (Abarca-Vargas et al, 2016;Namvar et al, 2017). Previous research conducted on S. palustris also indicated that alkaloid and phenolic groups were possible compounds responsible for the plant's AGI activity (Chai et al, 2015;Leng, 2016).…”
Section: Impact Of Harvesting Technique and Extraction Solventmentioning
confidence: 92%